The Relationship Between Fast Food Consumption Habits and Nutritional Status Among Female Adolescents at SMP Negeri 6 Pekanbaru - Wira Maria Ginting; Theresia Manik (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Adolescents in the transitional and growth phase are vulnerable to nutritional problems, including both undernutrition and overweight/obesity; therefore, adequate and balanced nutritional intake is essential during this period. However, current lifestyle and dietary changes have led to an increased consumption of fast food among the population, particularly among female adolescents. Fast food is typically high in calories, fat, sugar, and salt, and excessive consumption may lead to calorie accumulation, thereby affecting an individual’s nutritional status. This study aimed to analyze the relationship between fast food consumption habits and the nutritional status of female adolescents at SMP Negeri 6 Pekanbaru. This study employed a descriptive design with a cross-sectional approach. The study population consisted of 293 eighth-grade female students, with a sample of 66 respondents selected using simple random sampling. Data on fast food consumption were collected through interviews using a Food Frequency Questionnaire (FFQ), while nutritional status data were obtained from measurements of height and weight, which were then calculated using the Z-Score (BMI-for-age) formula. Data were analyzed using univariate and bivariate analyses with the Chi-Square statistical test. The results showed that respondents who frequently consumed fast food tended to have a higher prevalence of overnutrition (46.7%), whereas those who rarely consumed fast food mostly had normal nutritional status (72.2%). The Chi-Square test yielded a p-value of 0.002 (<0.05), indicating a significant relationship between fast food consumption habits and the nutritional status of female adolescents at SMP Negeri 6 Pekanbaru.